Contractual relationships in the Hungarian milk sector - Lajos Zoltán Bakucs; Imre Fertő; Gábor G. Szabó (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
In this paper we present an empirical analysis of farmers' contracting choice in the Hungarian milk sector using 2005 milk producer survey data, employing transaction cost economics. We focus on analysing some key determinants of farmers' contracting choices: type of contracts, duration, number of contractors, incentives provided in the contract and business history of farmers and buyers. Some of the main results include the importance and effect of farm size, quantity of milk delivered, planned short and long run or contract related investment on farm, the possibility of farmer to influence prices on the contracting choices.
Keywords: 330; transaction costs; contracts; milk products; Hungary